Removal of Cu(II) from Industrial Effluents by Citric Acid Modified Rice Straw (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2014)
The aim of the present study was to convert rice straw, a by-product of rice production to a metal adsorbent and investigate the potential of using the adsorbent for the removal of Cu (II) ions. The rice straw was modified with citric acid (CA) to enhance its nature's adsorption capacity. Batch adsorption studies of Cu (II) adsorption were carried out under various operating conditions, and found to be pH, initial adsorbate concentration, contact time, and temperature dependent. Experimental data were analyzed using the Langmuir and Freudlinch isotherm models, and can be well described by the Langmuir isotherm model that supports the assumption that adsorption takes place by single layer on homogeneous surfaces. Kinetic studies indicated that pseudo-second-order kinetic equation provides better data correlation than pseudo-first-order kinetic model. Thermodynamic studies show that the standard Gibbs free energy of the process at all temperatures was negative and changed with temperature increase, indicatinga spontaneous processthat increases with temperature. CA modified rice straw (CARS) shows a considerable potential as a low-cost and highly efficient biomaterial to be a new single-use adsorbent for Cu (II) ions removal from wastewater.
Keywords: Adsorption, citric acid, rice straw, copper ions, wastewater